Chlamydia pneumoniae and chronic bronchitis: association with severity and bacterial clearance following treatment. Issue 8 (1st August 2002) - Blasi, F; Damato, S; Cosentini, R; Tarsia, P; Raccanelli, R; Centanni, S; Allegra, L
Abstract : Background: A study was undertaken to evaluate Chlamydia pneumoniae chronic infection, other respiratory infections, and functional impairment in patients with chronic bronchitis (stage 1) and to examine chronic C pneumoniae infection, rate of acute exacerbations of chronic bronchitis, and rate of C pneumoniae eradication following antibiotic treatment (stage 2). Methods: In the stage 1 study respiratory specimens from 42 patients with steady state chronic bronchitis were analysed for Gram staining, sputum culture, and C pneumoniae DNA detection by nested touchdown polymerase chain reaction (PCR). On the basis of the results of stage 1, a second population of 141 consecutive patients with steady state mild to moderate chronic bronchitis (FEV1 ≥50% predicted) was studied. On admission, at regular intervals, and at exacerbation all patients underwent serological testing for C pneumoniae (microimmunofluorescence) and a nested touchdown PCR to detect C pneumoniae DNA was performed on peripheral blood mononuclear cells (PBMCs). Patients were assessed over a 12 month period. Information regarding the previous 12 months was taken from medical records. Results: Chronic colonisation of the sputum with C pneumoniae was significantly associated with lower FEV1 and greater airway bacterial colonisation. On admission to the stage 2 study, 80 patients were PCR negative and 61 were PCR positive. Over the 2 years a mean (SD) of 1.43 (1.32) acute exacerbations occurred in PCR negative patients and 2.03 (1.21) in PCR positive patients (p<0.01). During the 12 month follow up period 34 PCR positive patients had acute exacerbations and were treated with azithromycin for 6 weeks. Serological evidence of acute C pneumoniae reinfection/reactivation was found in two of the 34 patients. The rate of C pneumoniae DNA clearance from blood following treatment was 29% at follow up. Conclusion: Chronic colonisation with C pneumoniae is associated with a higher rate of exacerbations of chronic bronchitis. Long term treatment is required to obtain clearance of the organism from the blood.